Clipping and blending in Hausa / Maryam Maimota Shehu - Maimota Shehu, Marya (2015)
Words are the basic building blocks of a language. In everyday usage of a language, words are used and new words are formed and reformed in order to contain and accommodate all entities, phenomena, qualities and every aspect of the entire life. This research study seeks to examine some of the word formation processes and how they are used in forming new words in the Hausa language. The study focuses its main attention on clipping and blending as word formation processes and how these processes are used in the formation of words in the Hausa language. The research attempts to find answers to the following research questions: 1)What types of clipped and blended forms are found and how they are formed in the Hausa language? 2) How these clipped and blended forms function in Hausa language in different contexts? Findings of the study show that, there exist new types of words formed in Hausa language under blending, which previous studies did not either reveal or explain in detail. The data of this study was gathered from newspaper articles, and dictionary of Hausa language. The study also used Dressler (1985) as its main theoretical framework.